Pengaruh Tingkat Kesejahteraan Keluarga Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Sosiologi di SMAN 19 Kabupaten Tangerang - Janu Shyam Bachtiar; Septi Kuntari; Yustika Irfani Lindawati (Universitas Lambung Mangkurat, 2024)
The focus of this research is student learning achievement which is caused by the level of family welfare. The aims of this research are 1) To find out whether there is an influence of the level of family welfare on student learning achievement in sociology subjects at SMAN 19 Tangerang Regency, 2) To find out how much influence the level of family welfare has on student learning achievement in sociology subjects at SMAN 19 Tangerang Regency. Data collection techniques use questionnaries, interviews and documentation. The sampling technique used was purposive sampling technique, in this study the samples chosen were 2 (two) classes, namely XI IPS 3 and XI IPS 4 for the 2022/2023 academic years. The results of research showed that 1) Based on linear regression analysis show that the regression equation is Ŷ = 90,671 – 0,027X, so that an r2 value of 0,005 or 0,5% is obtained. This shows that there is a negative and insignificant influence on the level of family welfare on student learning achievement in sociology subjects at SMAN 19 Kabupaten Regency it was 0,5%. 2) Based on the analysis of the stages of a prosperous family according to the BKKBN the respondents is in the prosperous family category 3, 3) Based on the analysis of learning achievement the respondents is in the high achievement category, In the end, analysis of Maslow’s hierarchy of needs theory, students go to school to feel secure about their future and students go to school to get good achievements so as to improve their social status.